Programa computacional para avaliação da uniformidade e eficiência de aplicação em sistemas de irrigação por pivô central sob condições de quimigação - Souza, Paula Cristina de (2006)
Considering the importance of the evaluation of irrigation systems by central pivot with objective of determining its operational characteristics and its correct handling, the present work had as objective the elaboration of the proPIVÔ program, for Windows environment, in Visual language, which helps technicians to obtain efficiency values, in potential, of application and uniformity coefficients for irrigation systems by central pivot, and also determines the uniformity of distribution of chemical products applied by irrigation water tract. Besides, this program constitutes a didactic resource, due to the simplicity of its use, the several alternatives of data manipulation and the graphs and maps which can be obtained. The program uses an Access data base to store the rehearsals/tests, it calculates values of Heermann uniformity coefficient and Evans interpolated coefficient, generating graphs, space maps and reports.